Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/apa.14829
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a 24‐year tuberculosis screening in first‐grade elementary schoolers in a low‐burden area

Abstract: Aim: Early diagnosis of tuberculosis infection can significantly contribute to the control of the disease. The aim of the present study was to describe the tuberculin skin test (TST) trends over a 24-year period (1990-2013) and explore the value of universal tuberculosis screening in a low-burden area.Methods: All first graders that underwent TST during the 24-year study period on the island of Crete, Greece, were retrospectively included in the study.Results: A total of 82 402 children (92.3% of Greek natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Switch from a universal BCG vaccination policy for 6-yearold children at school entry to a targeted vaccination policy for high-risk neonates at birth was necessary due to a reduction in pediatric TB incidence during the past 2 decades. [5][6][7][8] Change in policy was in accordance with the International Union against Tuberculosis and Lung Disease criteria for discontinuation of universal BCG vaccination programs in countries with low TB prevalence. 10 The newly-adopted BCG vaccination policy at birth offers an ideal opportunity to surpass barriers related to the accessibility of vaccination services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Switch from a universal BCG vaccination policy for 6-yearold children at school entry to a targeted vaccination policy for high-risk neonates at birth was necessary due to a reduction in pediatric TB incidence during the past 2 decades. [5][6][7][8] Change in policy was in accordance with the International Union against Tuberculosis and Lung Disease criteria for discontinuation of universal BCG vaccination programs in countries with low TB prevalence. 10 The newly-adopted BCG vaccination policy at birth offers an ideal opportunity to surpass barriers related to the accessibility of vaccination services.…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence of TB in children in Greece decreased significantly over the past 2 decades, while immigrant children comprised an increasing proportion of diagnosed cases, including MDR-TB cases. [5][6][7][8] A hospital-based retrospective study in Athens, Greece of all (321) children <14 years with active TB diagnosed during 2000-2009 revealed that one-third of them originated from highly endemic countries. 5 In addition, immigrant children accounted for 61% of extra-pulmonary TB cases and for most MDR-TB cases.…”
mentioning
confidence: 99%